Doing better rather than promising more: a basic principle applicable to both climate modelling and climate policies - Douville, H. (2025)
A growing number of scientists are expressing concerns about the inadequacy of climate change policies. Fewer are questionning the dominant climate modelling paradigm and the IPCC’s success to prevent humanity from venturing unprepared into hitherto unknown territories. However, in view of an urgent need to provide readily available data on constraining uncertainty in local and regional climate change impacts in the next few years, there is a debate on the most suitable path to inform both mitigation and adaptation strategies. Examples are given how both common statistical methods and emerging technologies can be readily used to exploit the wealth of existing knowledge to drive adaptation policy. Parsimonious and equitable approaches on constraining uncertainty are promoted that combine various lines of evidence, including model diversity, large ensembles, storylines, and novel statistical methods applied on well-calibrated, global and regional, Earth System simulations, to deliver more reliable climate information. As examplified by the Paris agreement on desirable global warming targets, it is argued that the display of unrealistic ambitions may not be the best way for climate modellers to accomplish their long-term objectives, especially given the growing consensus on climate emergency and the allocated short time for the knowledge to be delivered and applied.